Accurate prediction of standard enthalpy of formation based on semiempirical quantum chemistry methods with artificial neural network and molecular descriptors. Issue 2 (29th August 2020) - Wan, Zhongyu; Wang, Quan‐De; Liang, Jinhu
Abstract: This work investigates possible improvements in the accuracy of semiempirical quantum chemistry (SQC) methods for the prediction of standard enthalpy of formation (Δf H o ) through the use of an artificial neural network (ANN) with molecular descriptors. A total of 142 organic compounds with enough structural diversity has been considered in the training set. Standard enthalpy of formation for the selected compounds at the semiempirical PM3 and PM6 quantum chemistry methods is collected from literature and is calculated by using the semiempirical PM7 method in this work. The multiple stepwise regression is first used to screen effective molecular descriptors, which are highly correlated with the error terms of the standard enthalpy of formation compared with experimental values. The obtained seven effective molecular descriptors are then used as input set to establish three 7‐11‐1 neural network‐based correction models to improve the accuracy of SQC methods. By using the developed correction models, the mean absolute errors for Δf H o of PM3, PM6, and PM7 methods are reduced from 22.36, 18.60, and 17.27 to 9.86, 9.83, and 8.95, respectively, in kJ/mol. Meanwhile, the results of the test set show that the neural network does not have the problem of overfitting. Detailed analysis of the seven effective molecular descriptors indicates that the major source of the correction models is the electron‐withdrawing effect. The developed ANN models for the three selected SQC methods provide an efficient method for the quick and accurate prediction of thermodynamic properties. Abstract : The semi‐empirical quantum chemistry method has excellent calculation speed, but its accuracy is very worrying. This work takes the difference between the experimental value and the calculated value of SQC as the target, combined with artificial neural network. Using descriptors that do not need to solve the Schrödinger equation as the input of the artificial neural network for fitting. The method we put forward has good accuracy while ensuring faster calculation speed.